Handbook of oil spill science and technology - Fingas, Mervin F. (Wiley, 2015)
Provides a scientific basis for the cleanup and for the assessment of oil spillsEnables Non-scientific officers to understand the science they use on a daily basisMulti-disciplinary approach covering fields as diverse as biology, microbiology, chemistry, physics, oceanography and toxicologyCovers the science of oil spills from risk analysis to cleanup and through the effects on the environmentIncludes case studies examining and analyzing spills, such as Tasman Spirit oil spill on the Karachi Coast, and provides lessons to prevent these in the future.